Burn notice. Season two [videorecording (DVD)] - Donovan, Jeffrey; Anwar, Gabrielle; Campbell, Bruce, 1958-; Gless, Sharon; Nix, Matt (20th Century Fox Home Entertainment, 2009)
After being mysteriously blacklisted from the intelligence community, former CIA operative Michael Westen must rely on his extraordinary and lethal set of skills to survive the hardboiled streets of Miami and somehow recover his stolen identity. With the help of Fiona, his sultry ex-girlfriend and a former IRA affiliate, she is every bit as deadly as she is gorgeous. Michael must track down his elusive nemesis and get to the bottom of his burn.